2007
DOI: 10.1016/j.nurt.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Glatiramer Acetate in Treatment of Multiple Sclerosis

Abstract: Summary:Glatiramer acetate (GA) (Copolymer-1, Copaxone, Teva, Israel, YEAK) is a polypeptide-based therapy approved for the treatment of relapsing-remitting multiple sclerosis. Most investigations have attributed the immunomodulatory effect of GAs to its capability to alter T-cell differentiation. Specifically, GA treatment is believed to promote development of Th2-polarized GA-reactive CD4 ϩ T-cells, which may dampen neighboring inflammation within the central nervous system. Recent reports indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 71 publications
3
85
0
4
Order By: Relevance
“…Mice were scored as follows: 0, no symptoms; 1, decreased tail tone; 2, mild monoparesis or paraparesis; 3, severe paraparesis; 4, paraplegia and/or quadriparesis; and 5, moribund condition or death. Mice received daily s.c. injections of 150 g GA suspended in PBS solution (n ϭ 3) or PBS solution alone (n ϭ 3) starting 7 days before EAE induction as described elsewhere (42). All experiments were carried out in accordance with guidelines prescribed by the Institutional Animal Care and Use Committee at the University of California, San Francisco.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were scored as follows: 0, no symptoms; 1, decreased tail tone; 2, mild monoparesis or paraparesis; 3, severe paraparesis; 4, paraplegia and/or quadriparesis; and 5, moribund condition or death. Mice received daily s.c. injections of 150 g GA suspended in PBS solution (n ϭ 3) or PBS solution alone (n ϭ 3) starting 7 days before EAE induction as described elsewhere (42). All experiments were carried out in accordance with guidelines prescribed by the Institutional Animal Care and Use Committee at the University of California, San Francisco.…”
Section: Methodsmentioning
confidence: 99%
“…In a positive feedback loop, Th2 cells reciprocally modify APC function, pushing APCs toward the anti-inflammatory type II phenotype (Kim et al 2004;Vieira et al 2003;Weber et al 2007a). Accordingly, upon exposure to GA, human dendritic cells induce IL-4-secreting Th2 cells and increased levels of anti-inflammatory IL-10 ( Vieira et al 2003); and T-cell-mediated deviation of APC toward a type II cytokine pattern has been demonstrated in human microglial cells exposed to GA-reactive T cells from MS patients (Kim et al 2004).…”
Section: Interplay Between Apcs and T Cellsmentioning
confidence: 99%
“…However, studies in MS patients and EAE models have demonstrated that continued exposure to GA induces a shift from a primarily Th1-type cytokine profile to a Th2-type profile, characterized by increased secretion of IL-5 and IL-13 (Aharoni et al 1997;Chen et al 2001;Duda et al 2000;Franciotta et al 2003;Miller et al 1998;Neuhaus et al 2000;Sanna et al 2006;Weder et al 2005). GA-specific Th2 cells are also the source of anti-inflammatory cytokines such as IL-4, IL-6, IL-10, (Aharoni et al 1997) and brain-derived neurotrophic factor (BDNF) (Aharoni et al 1997(Aharoni et al , 2000Azoulay et al 2005;Miller et al 1998;Putheti et al 2003;Weber et al 2007a;Ziemssen et al 2005). A similar shift to anti-inflammatory cytokines is also observed in the colons of mice with 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis (Aharoni et al 2005c).…”
Section: Cd4 + T-cell Responsesmentioning
confidence: 99%
“…When compared with placebo, interferon beta has been shown to increase the time between relapses by between 3 and 5 months and decreases the risk of further relapse by 27-33% [39]. Glatiramer acetate, a modulator of T-cell differentiation [40] has a similar effect on relapse rate, but does not control MRI gadolinium enhancement in the early stages of treatment as well as interferon beta [41].…”
Section: Interferon Beta and Glatiramer Acetatementioning
confidence: 99%